Improving dispute settlement in the World Trade Organization : the Dispute Settlement Understanding Review - making it work? - Mercurio, Bryan (2004)
Evaluates the Review of the Dispute Settlement Understanding (DSU Review) in the World Trade Organization. Provides the background to the DSU Review negotiation process, evaluates party positions on the key issues of the Review and makes suggestions that should not only help members conclude the DSU Review, but also improve the effectiveness and efficiency of the DSU. Puts forward five reasons why the DSU Review has not been completed. Recommends that the more controversial proposals be studied and fully evaluated so that members can be aware of the potential benefits and drawbacks of the proposed changes and, when appropriate, make informed decisions on the issues.